2019
DOI: 10.1007/s00300-019-02480-w
|View full text |Cite
|
Sign up to set email alerts
|

Underwater photogrammetry in Antarctica: long-term observations in benthic ecosystems and legacy data rescue

Abstract: Ecological studies about marine benthic communities received a major leap from the application of a variety of non-destructive sampling and mapping techniques based on underwater image and video recording. The well-established scientific diving practice consists in the acquisition of single path or 'round-trip' over elongated transects, with the imaging device oriented in a nadir looking direction. As it may be expected, the application of automatic image processing procedures to data not specifically acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
0
32
0
Order By: Relevance
“…TNB is often ice-free during polar summer months and span for about 64 km along the coast of Victoria Land, being comprised between Cape Washington and the Drygalski Ice Tongue. It represents an important site for longterm research on the marine ecology of benthic communities (e.g., Piazza et al, 2019Piazza et al, , 2020, supporting rich and complex sponge and anthozoan communities, alongside loosely structured and low diversity assemblages, often coexisting in mosaics (e.g., Sarà et al, 1992;Cattaneo-Vietti et al, 1997;Gambi et al, 1997;Cerrano et al, 2009).…”
Section: Sampling Areamentioning
confidence: 99%
“…TNB is often ice-free during polar summer months and span for about 64 km along the coast of Victoria Land, being comprised between Cape Washington and the Drygalski Ice Tongue. It represents an important site for longterm research on the marine ecology of benthic communities (e.g., Piazza et al, 2019Piazza et al, , 2020, supporting rich and complex sponge and anthozoan communities, alongside loosely structured and low diversity assemblages, often coexisting in mosaics (e.g., Sarà et al, 1992;Cattaneo-Vietti et al, 1997;Gambi et al, 1997;Cerrano et al, 2009).…”
Section: Sampling Areamentioning
confidence: 99%
“…This is acceptable as the water column in between the ice and the enclosure was <1.1 m and our site was characterized by exceptionally clear waters (see Figure 4c). Antarctic surface waters are generally considered to have low particle loads with low backscattering (e.g., [121]). Nonetheless, as we increase sensor distance from the target, or in case of consistent under-ice phytoplankton abundance (e.g., [122]), the impact of the water column should be addressed with standard color correction approaches for RGB imagery [44,123,124] and for the water column correction of hyperspectral radiometric data if possible [44,125].…”
Section: Caveats and Future Challengesmentioning
confidence: 99%
“…These features are tracked from one image to another, enabling initial estimates of the camera position and object coordinates that are then refined iteratively by means of nonlinear least squares minimization [23,24]. Then, MVS finds correspondences between stereo images and applies regularization in the object space to produce 3D dense point clouds [25,26]. Indeed, SfM-MVSs are considered to be rapid and low-cost tools for producing scaled, 3D digital models and orthophoto mosaics, while also automatically resolving the distortions of underwater refraction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of SfM-MVS as another tool for reef monitoring [27,28], long term monitoring of benthic communities and legacy data rescue [25], monitoring the demography and morphometry of soft corals such as gorgonian species [29], large underwater area 3D reconstruction [30], and bathymetry determination [31][32][33]. Moreover, Burns et al [22], Figueria et al [34], and Leon et al [28] used SfM-MVS to measure multiple metrics of 3D habitat complexity, providing accuracy measurements, and computed rugosities.…”
Section: Introductionmentioning
confidence: 99%